Continuing to care for people with dementia: Irish family carers' experience of their relative's transition to a nursing home - Argyle, Elaine; Downs, Murna; Tasker, Jessica (University of Bradford, 2010)
The purpose of this study is to describe carers’ experience of the transition of their relative who has dementia to nursing home care. It is intended that this will provide evidence-based guidance for the development of initiatives to support carers. This aim is addressed by answering the following questions: